2009
DOI: 10.1109/tuffc.2009.1229
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Measurement of Human Subcutaneous Fat with Ultrasound

Abstract: Measuring human subcutaneous fat is useful for assessing health risks due to obesity and for monitoring athletes' health status, body shapes and weight for various sports competitions such as gymnastics and wrestling. Our aim is to investigate the use of ultrasound imaging in automatically measuring human subcutaneous fat thickness.We proposed to use the spectrum properties extracted from the raw radio frequency (RF) signals of ultrasound for the purpose of fat boundary detection. Our fat detection framework c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Ng et al [8] recently showed that changes in the spectral content of 2D-spatial RF images enabled to accurately measure subcutaneous layer thickness on humans, but required spatial compounding. In this paper, a real-time implementation of the spectral analysis proposed by Ng et al [8], but applied to 1D ultrasound RF lines, was evaluated and compared to the exploitation of the IBS parameter from [7].…”
Section: Introductionmentioning
confidence: 99%
“…Ng et al [8] recently showed that changes in the spectral content of 2D-spatial RF images enabled to accurately measure subcutaneous layer thickness on humans, but required spatial compounding. In this paper, a real-time implementation of the spectral analysis proposed by Ng et al [8], but applied to 1D ultrasound RF lines, was evaluated and compared to the exploitation of the IBS parameter from [7].…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies were dedicated to automated lesion segmentation based on RF data 27 33 . Unprocessed backscattered US data contain information about US scatterer density.…”
mentioning
confidence: 99%
“…Segmentation Phase: The fat region was delineated from the grayscale image using Otsu's thresholding method. According to a previous study by Ng, et al [26], the fat content will appear as brighter pixels in a grayscale image compared to other components due to its higher impedance mismatch with muscle tissue. 4.…”
Section: Image Preprocessing: An Image Enhancement Technique Called Imentioning
confidence: 95%
“…With implementation of image processing, the speckle noise from B-mode imaging can be minimized and thus improve the process of determining fat content from images [26]. It has been proven that ultrasound Bmode imaging can be used to visualize components of beef, lamb and chicken, i.e.…”
Section: Ultrasoundmentioning
confidence: 99%